Research and application progress of abandoned mine compressed air energy storage - Longxuan WANG; Wen ZHANG; Xiaolin YANG; Xiaoming CONG; Hanxun WANG; Xinyu WANG; Yongkang LONG (Meitan kexue jishu)
In the backdrop of the increasingly severe global climate situation, the demand for renewable energy is continuously expanding worldwide to achieve carbon neutrality goals. However, due to the intermittent and unstable nature of renewable energy sources such as wind and solar power, large-scale commercial utilization is hindered. Energy storage technology can effectively address the integration and grid connection issues of large-scale renewable energy. Among these technologies, Abandoned Mine Compressed Air Energy Storage (AM-CAES) has garnered widespread attention in the field of energy storage both domestically and internationally due to its favorable ecological and economic benefits. Based on this, relevant research on AM-CAES was summarized in this paper, elucidating its fundamental principles and the then-current status of thermodynamic model derivation. The theoretical research progress of AM-CAES in four aspects: site selection suitability, operational efficiency, safety, environmental impact, and economic feasibility, was studied. The characteristics of domestic and foreign AM-CAES demonstration projects and their ecological and economic benefits were analyzed. A comparison of AM-CAES-related policies between different countries was made. Finally, the paper summarized and discussed the scientific challenges AM-CAES still faced in both technological and economic aspects. The conclusion indicated that utilizing existing abandoned mine shafts for compressed air energy storage could significantly reduce engineering investment, minimize the development of new land resources, and exhibit high environmental friendliness. Moreover, it could help balance energy supply and demand, enhance grid stability, promote the integration of renewable energy, and thus reduce the proportion of high-carbon electricity, with broad application prospects. Currently, AM-CAES still awaited further breakthroughs in energy storage efficiency, storage cycle, and system scale, while the scale of investment and revenue models also required relevant policies to be enacted to drive and refine them. It aims to provide scientific references for the sustainable utilization of abandoned underground space resources and the storage and conversion of renewable energy, thereby contributing to China’s ecological restoration and energy transition efforts.